Four approaches to guide ecological restoration in Latin America. Issue 2 (2nd December 2016) - Meli, Paula; Herrera, Francisco F.; Melo, Felipe; Pinto, Severino; Aguirre, Nicolay; Musálem, Karim; Minaverry, Clara; Ramírez, Wilson; Brancalion, Pedro H. S.
Abstract: There is strong upswing in conservation and restoration efforts in Latin America (LA), particularly in the recent decades after several countries have committed to international agreements such as the Aichi targets of the Convention on Biological Diversity, Initiative 20×20, and the Bonn Challenge. To fulfill these agreements, the practice of ecological restoration has to be defined based on ecological knowledge, but also on the specific social, economic, and legal aspects of each country in the region. Here, we give some examples about the national understanding of ecological restoration in 10 countries of LA. We identify difficulties and opportunities to define restoration priorities and needs, and discuss some approaches to cope with economic constraints and agreements, including the potential role of restoration networks in this process. On the basis of the socioecological complexity of these countries and the expectations they have in relation to restoration, we proposed four approaches to guide restoration practice and policy in the region: (1) including biodiversity and ecosystem services approach into ecosystem restoration initiatives; (2) promoting restoration in their frequently human‐modified landscapes; (3) accounting for cost–benefit trade‐offs; and (4) assembling "horizontal" communication frameworks. These approaches should be based at national levels, but adapted to local‐regional levels, in a bottom‐up perspective. We consider that national and international restoration networks in the region can help to overcome difficulties, fostering a solid scientific community, helping to develop national approaches that better match the specific conditions of each country and enhancing communication among different groups of stakeholders.